Engines of Patriarchy: Ethical Artificial Intelligence in Times of Illiberal Backlash Politics - Hendrik Schopmans; Jelena Cupać (Ethics & International Affairs, 2021)
In recent years, concerns over the risks posed by artificial intelligence (AI) have mounted. In response, international organizations (IOs) have begun to translate the emerging consensus on the need for ethical AI into concrete international rules and standards. While the path toward effective AI governance faces many challenges, this essay shifts attention to an obstacle that has received little attention so far: the growing illiberal backlash in IOs. Prompted by Poland's recent rejection of a European position on AI due to the document's mention of “gender equality,” we argue that Poland followed a strategy that illiberal actors now regularly employ in IOs. To combat gender norms and women's rights across issue areas, illiberal contesters first identify the progressive language in international documents and then threaten to veto those documents—unless such language is watered down or removed. This spoiling strategy, we argue, may not only lead to the compromising of fundamental human rights norms but may also prevent much needed rules for AI from being adopted altogether. Against this background, we urge scholars and practitioners concerned with AI ethics to pay closer attention to illiberal backlash politics. IOs are emerging as spaces where progressive AI rules and standards are increasingly contested—and where they need to be defended to safeguard fundamental rights in an age of rapid technological change.
Keywords: 300; artificial intelligence; ethics; backlash; gender equality; liberal international order; gender bias